Isolation, Production and Media Optimization of Cellulase-Producing Microbes from Coir Industry Waste Soil - Eglin Juno B K; Dr. A L Hema Latha (The Bioscan, 2026)
Cellulases are enzymes mainly used for the hydrolysis of lignocellulosic biomass. It has wide industrial applications such as biofuels, textiles, pulp and paper, food and feed, and pharmaceuticals. The coir industry generates large volumes of cellulosic waste, providing an abundant, low-cost, and cellulose-rich niche for cellulolytic microorganisms. This study reports the isolation of cellulase-producing bacteria from coir industry waste soil, evaluates the cellulolytic potential, and systematically optimizes culture conditions and medium composition to maximize cellulase production. Soil samples were collected from the coir processing sites, serially diluted, and plated on Carboxymethyl Cellulose (CMC) agar.